Olive Mill Wastewater Polyphenol-Enriched Fractions by Integrated Membrane Process: A Promising Source of Antioxidant, Hypolipidemic and Hypoglycaemic Compounds - Rosa Tundis; Carmela Conidi; Monica R. Loizzo; Vincenzo Sicari; Alfredo Cassano (MDPI AG, 2020)
The valorisation of food wastes is a challenging opportunity for the green, sustainable, and competitive development of industry. The recovery of phenols contributes to the sustainability of olive waste sector, reducing its environmental impact and promoting the development of innovative formulations of interest for pharmaceutical, nutraceutical, and cosmeceutical applications. In this work, olive mill wastewater was treated through a combination of microfiltration (MF), nanofiltration (NF), and reverse osmosis (RO) in a sequential design to produce polyphenol-enriched fractions that have been investigated for their chemical profile using ultra-high-performance liquid chromatography (UHPLC), and their potential antioxidant, hypolipidemic, and hypoglycaemic activities. RO retentate exhibited the highest content of hydroxytyrosol, tyrosol, oleuropein, verbascoside, vanillic acid, and luteolin. In particular, a content of hydroxytyrosol of 1522.2 mg/L, about five times higher than the MF feed, was found. RO retentate was the most active extract in all in vitro tests. Interestingly, this fraction showed a 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic) acid (ABTS) radicals scavenging activity with an IC50 value of 6.9 μg/mL and a potential inhibition of lipid peroxidation evaluated by the β-carotene bleaching test with IC50 values of 25.1 μg/mL after 30 min of incubation. Moreover, RO retentate inhibited α-amylase and α-glucosidase with IC50 values of 65.3 and 66.2 μg/mL, respectively.